2003
DOI: 10.1046/j.1365-2486.2003.00641.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in the effects of elevated CO2 on rice at three levels of nitrogen supply: a free air CO2 enrichment (FACE) experiment

Abstract: Over time, the stimulative effect of elevated CO2 on the photosynthesis of rice crops is likely to be reduced with increasing duration of CO2 exposure, but the resultant effects on crop productivity remain unclear. To investigate seasonal changes in the effect of elevated CO2 on the growth of rice (Oryza sativa L.) crops, a free air CO2 enrichment (FACE) experiment was conducted at Shizukuishi, Iwate, Japan in 1998–2000. The target CO2 concentration of the FACE plots was 200 µmol mol−1 above that of ambient. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

18
139
2
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 192 publications
(161 citation statements)
references
References 27 publications
18
139
2
2
Order By: Relevance
“…Under elevated [CO2], despite a significant increase in root biomass (data not shown), as has open been reported ( (Kim et al, 2003;Ziska and Bunce, 2007;Yang et al, 2007), the root : shoot ratio was not altered in this study. This suggested that elevated [CO2] is unlikely to change the balance between above-and below-ground developments of rice cultivar used (i.e.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Under elevated [CO2], despite a significant increase in root biomass (data not shown), as has open been reported ( (Kim et al, 2003;Ziska and Bunce, 2007;Yang et al, 2007), the root : shoot ratio was not altered in this study. This suggested that elevated [CO2] is unlikely to change the balance between above-and below-ground developments of rice cultivar used (i.e.…”
Section: Discussionsupporting
confidence: 85%
“…Early studies reported that although elevated [CO2] increases tiller number of rice crops, this stimulatory effect is only significant up to heading but a relatively minor afterward (Kim et al, 2003). A similar response fashion to elevated [CO2] was also reported for leaf area of rice plants (Kim et al, 2003;Sakai et al, 2006). Such changes in plant height, tiller and leaf area under elevated [CO2] and/or Ta will have the potential to modify in plant architecture at whole-plant or canopy level.…”
mentioning
confidence: 52%
See 3 more Smart Citations